CHARACTERISTIC OF AIRBORNE PARTICULATE MATTER SAMPLES COLLECTED FROM TWO SEMI INDUSTRIAL SITES IN BANDUNG, INDONESIA - Diah Dwiana Lestiani; Muhayatun Santoso; Syukria Kurniawati; Andreas Markwitz (Indonesian Journal of Chemistry, 2013)
Air particulate matter concentrations, black carbon as well as elemental concentrations in two semi industrial sites were investigated as a preliminary study for evaluation of air quality in these areas. Sampling of airborne particulate matter was conducted in July 2009 using a Gent stacked filter unit sampler and a total of 18 pairs of samples were collected. Black carbon was determined by reflectance measurement and elemental analysis was performed using particle induced X-ray emission (PIXE). Elements Na, Mg, Al, Si, P, S, Cl, K, Ca, Ti, Cr, Mn, Fe, Cu, Zn and As were detected. Twenty four hour PM2.5 concentration at semi industrial sites Kiaracondong and Holis ranged from 4.0 to 22.2 µg m-3, while the PM10 concentration ranged from 24.5 to 77.1 µg m-3. High concentration of crustal elements, sulphur and zinc were identified in fine and coarse fractions for both sites. The fine fraction data from both sites were analyzed using a multivariate principal component analysis and for Kiaracondong site, identified factors are attributed to sea-salt with soil dust, vehicular emissions and biomass burning, non ferrous smelter, and iron/steel work industry, while for Holis site identified factors are attributed to soil dust, industrial emissions, vehicular emissions with biomass burning, and sea-salt. Although particulate samples were collected from semi industrial sites, vehicular emissions constituted with S, Zn and BC were identified in both sites.